Post Harvest Handling of Fish Through the Cold Chain at UPR Mandiri Abadi - Rarassari, Madyasta Anggana; Saadah, Raudhatus; Inayatullah, Ahlam; Khairunnisa, Eka Nurriza; Ritonga, Nia Boru; Riani, Ira Gusti; Utami, Aldilla Sari; handayani, martatika; Puteri, Rizki Eka; Sari, Selly Ratna (Jurnal Pengabdian Masyarakat, 2024)
Purpose: UPR Mandiri Abadi is a community hatchery unit that focuses on catfish production at the grow-out stage. The rearing process is carried out for three months with the harvest of catfish weighing 1 kg per 6 fish. Currently, catfish distribution is mostly in the South Sumatra area, such as restaurants and catfish pecel sellers. Because the distance is up to two hours between the UPR location in Kenten and the sales area in Indralaya, post-harvest handling using cold chains is the right solution to maintain fish quality. Method: In this service activity, the team provided counseling to UPR Mandiri Abadi members regarding post-harvest fish handling techniques using cold chains. Members actively participated by asking various questions regarding good cold chain procedures for fish shipments. Practical Applications: This service activity also includes training and outreach materials which are designed to be easily understood and applied by catfish farmers, especially in terms of shipping fish using a cold chain system. Conclusion: Through this outreach, UPR Mandiri Abadi can maintain the quality of fresher catfish so that it can attract more consumers and increase fish sales.